Ketotifen therapy in chronic graft-versus-host disease (cGVHD): effect on mast cells and fibroblasts. - Nagler, A (1995)
Current treatment options for cGVHD are limited. Mast cells (MC) and fibroblasts have been shown to play a role in the murine model of cGVHD. Ketotifen is an anti-H-1 antihistamine with MC-stabilizing properties. We therefore treated eight patients with cGVHD with ketotifen (6 micrograms/day for 3 months). Three additional age- and sex-matched cGVHD patients served as controls. MC count and activation state in cGVHD skin biopsies and the in vitro effect of peripheral blood mononuclear cell (PBMC) supernatants on (i) histamine release by MC; (ii) 3T3-fibroblast proliferation; and (iii) prostaglandin E2 (PGE2) production, were evaluated. Ketotifen therapy resulted in clinical improvement in 4/8 patients, stabilization of the disease in 2/8, while in 2/8 patients the cGVHD progressed and they died of bacterial sepsis. Side effects were minimal. In the skin biopsies the number of MC was found to be 0.58 +/- 0.17 (n = 8) (field x 400) and the MC looked degranulated (toluidine blue staining). Following ketotifen therapy MC number was increased to 1.2 +/- 0.28 (n = 8) (P < 0.05). PBMC supernatants of cGVHD patients stimulated histamine release from cultured rat MC (n = 8) (2.7 +/- 0.5 micrograms/ml; normal values are 2.1 +/- 0.4 micrograms/ml, n = 5). Ketotifen therapy reduced the histamine release level to the normal range (2.0 +/- 0.5 micrograms/ml, P < 0.05) (n = 8). Ketotifen therapy had no significant effect on: (i) 3T3 fibroblast proliferation which was suppressed by cGVHD PBMC supernatants; (ii) the elevated PGE2 production which we observed when fibroblasts were incubated with the PBMC supernatants. These results indicate that ketotifen may play a therapeutic role in cGVHD.